2018
DOI: 10.1080/14649365.2018.1454978
|View full text |Cite
|
Sign up to set email alerts
|

Placing ‘sustainability’ in context: narratives of sustainable consumption in Nanjing, China

Abstract: This article examines how ordinary people practice the notion of sustainable consumption in relation to their everyday lives and experiences of the wider environment and, further, how these understandings relate to public discourses of sustainability in contemporary China. The paper is based on an empirical analysis of 129 narrative interviews with local residents in urban Nanjing, collected as part of an interdisciplinary and international comparative research project. It argues that in popular narratives, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 43 publications
0
18
0
1
Order By: Relevance
“…Food safety has become a major concern of consumers throughout China [67]. In Nanjing, we found that three-quarters of surveyed household heads worry about the safety of their food on a daily basis [65,68]. Another recent study of narratives of sustainable consumption in Nanjing demonstrated similar deep-seated fears about contaminated food [69].…”
Section: Integrating Food Utilizationmentioning
confidence: 83%
“…Food safety has become a major concern of consumers throughout China [67]. In Nanjing, we found that three-quarters of surveyed household heads worry about the safety of their food on a daily basis [65,68]. Another recent study of narratives of sustainable consumption in Nanjing demonstrated similar deep-seated fears about contaminated food [69].…”
Section: Integrating Food Utilizationmentioning
confidence: 83%
“…In contemporary China, the discourse of convenience is deeply inscribed in people's daily consumption. As discussed elsewhere, Chinese consumers would rather give up the convenience created by modern technologies, even though their purchase of convenience could cause environmental or social problems (Liu et al, 2018). It is still unclear how the role of takeaway food or other convenience food in Chinese consumers' everyday life in the literature.…”
Section: Convenience and Food Consumptionmentioning
confidence: 99%
“…According to these quotations, the term of mianzi (can be translated directly as 'face' in English. It refers to a sense of favourable self-esteem, wealth and prestige) is centred to social hospitality norms in China, which results in a great amount of food wastes in restaurants (Liu et al, 2018). Although people tend to eat alone and therefore do not have to care about their mianzi in canteens, the tasteless but cheap food provided in these institutional eating spaces make them waste more.…”
Section: A Wasteful Lifestyle?mentioning
confidence: 99%
“…Sustainable consumption (A5) has emerged as a critical priority area in research and decision-making associated with sustainable development (Liu, Valentine, Vanderbeck, McQuaid, & Diprose, 2018). Providing eco-demand for the customer (C21) fulfills not only the physical and social needs for customers but also the consumption of green products and services (Horbach, Rammer, & Rennings, 2012;Tseng & Tan, 2016).…”
Section: The Proposed Measuresmentioning
confidence: 99%